Pengenalan Playback Theater sebagai Metode Berteater untuk Melepaskan Ketegangan - Riyana Rizki Yuliatin; Puspita Dewi; Hary Murcahyanto; Sandy Ramdhani; Hilda Hastuti (ADMA : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2021)
Various ways used to express ideas, feelings, and opinions. Art is one of the most effective modes to convey emotions. Playback theatre by combining artistic relation and social relation becomes a method applied. Playback theatre concerns with the telling process. Pre-test and post-test were conducted to identify the previous knowledge of the participants before providing materials and to recognize the knowledge after the activity. The empowerment activity results show that playback theatre has a positive impact on the participants to reduce nervously and it establishes chemistry between actors and music players so that the performance could be satisfied and better. It is expected that other lecturers or researchers implement and develop the playback theatre method to decrease tension and nervousness in playing roles as actors.